Detail experimental testing of unmanned aerial vehicles engine performance - Moganaraj, Murugiah (2013)
This project is about detail experimental testing of Unmanned Aerial Vehicles (UAV) engine performance. However, there is no proper selection of test bed available for the performance evaluation, testing and analysis of the UAV propulsion system. This project has two major objectives which are to design and fabricate a test bed for the UAV propulsion system and to conduct detail performance experimentations of the UAV propulsion system run at various speed. In this study, test bed model is designed to test the nitro engine Unmanned Aerial Vehicle (UAV) which is model of Thunder Tiger Pro36 Engine Series of aircraft performance. In addition, six performance parameters are recorded for testing of the engine performance, which are Thrust, shaft brake power, available power, propulsive efficiency, specific fuel consumption and thrust coefficient. Furthermore, the method used in this project is to identify the unknown variables in parameters by using some sensors. The results show that the fabricated test bed can be used to study the engine performance. Specifically, performance parameters are directly proportional to the engine speed. These results show that the performance parameters are increasing along with the speed. In conclusion, the fabricated test bed can be used for the testing of engine performance analysis. Outcomes of this experiment can be successful by using the test bed because it helps to reduce the cost and time for UAV propulsion performances testing.